The Behavior Avoidance Test: Association With Symptom Severity and Treatment Outcome in Obsessive-Compulsive Disorder - Hansmeier, Jana; Haberkamp, Anke; Glombiewski, Julia A.; Exner, Cornelia (Frontiers in Psychiatry, 2021)
Behavior therapy of obsessive-compulsive disorder (OCD) aims to reduce avoidance, rituals, and discomfort in OCD-relevant situations. The Behavioral Avoidance Test (BAT) measures these behavior-related outcomes in individually challenging OCD-related situations. The association of the BAT with OCD severity measures and its relevance for treatment outcome is, however, still unclear. The current study investigates with a retrospective analysis of a subsample of a pilot study, (1) if reactions on the BAT are related to OCD severity measures in an OCD sample (n = 28), (2) if treatment with two variants of cognitive-behavior therapy (exposure and response prevention versus metacognitive therapy) changes the BAT scores and (3) if these changes as well as pretreatment BAT avoidance are relevant for OCD treatment outcome as measured by the Yale-Brown Obsessive Compulsive Scale (Y-BOCS). Participants rated avoidance, ritual, and discomfort in three individually challenging OCD-related situations before and after therapy. For one of these situations, BAT dimensions were rated by the therapist and an independent rater in addition to the patients’ ratings. Correlational analyses found significant correlations between BAT discomfort and OCD severity measures like the Y-BOCS. A repeated measures ANOVA with pre- and posttest scores showed that all three BAT dimensions significantly decreased during both treatments. Hierarchical regression analyses (controlling for Y-BOCS pretest scores) revealed that changes in BAT discomfort as well as pretreatment BAT avoidance scores predicted the Y-BOCS posttest score. These findings suggest that the BAT is a distinct measure of behavior-related outcomes partly being relevant for OCD treatment outcome.